2018
DOI: 10.1007/s00415-018-8800-4
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment in Parkinson’s disease: the Parkinson’s disease cognitive study (PACOS)

Abstract: Approximately 30% of Parkinson's disease (PD) patients show impaired cognitive performance, which is suggestive of Mild Cognitive Impairment (MCI), representing a predictor of dementia, especially when present at diagnosis. The objective of the study was to evaluate the frequency and clinical predictors of MCI in a large hospital-based cohort of PD patients. We collected cross-sectional data from the Parkinson's disease cognitive impairment study (PACOS), a multicenter study involving two Movement Disorder cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 40 publications
12
95
1
2
Order By: Relevance
“…The prevalence rate computed here (40%) was very close to the value reported in previous cross‐sectional and longitudinal studies where PD‐MCI was identified by MDS criteria, but higher than the value reported in studies where MCI was defined by other clinical criteria . This difference underlines the clinical relevance of adopting uniform MDS criteria to identify PD‐MCI accurately.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The prevalence rate computed here (40%) was very close to the value reported in previous cross‐sectional and longitudinal studies where PD‐MCI was identified by MDS criteria, but higher than the value reported in studies where MCI was defined by other clinical criteria . This difference underlines the clinical relevance of adopting uniform MDS criteria to identify PD‐MCI accurately.…”
Section: Discussionsupporting
confidence: 81%
“…A total of 9 of 25 studies found that patients with PD‐MCI took higher LEDD than patients without PD‐MCI; our meta‐analysis confirmed this association (Supplementary Material 5; Table ), with a significant and positive ES (= 0.25). The heterogeneity among the studies was significant and moderate, but sensitivity analysis indicated stability of ES level, and there was no publication bias.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations